Forced folds and fractures - Cosgrove, J. W.; Ameen, Mohammed S. (Geological Society, 2000)
This detailed study of forced folds generated in a variety of situations focuses on the geometry and spatial organisation of these folds and their associated fracture patters. A comparison is made between forced folds and buckle folds.
Keywords: Folds (Geology); Rock deformation.; elektronické knihy; electronic books